Characterization of Caffeoylglucoside Derivatives and Hypouricemic Activity of the Ethyl Acetate Fraction from Aster glehni - Son, Min Jeoung; Jin, Changbae; Lee, Yong Sup; Lee, Jae Yeol; Kim, Hyoung Ja (WILEY-V C H VERLAG GMBH, 2015)
In the search for xanthine oxidase (XOD) inhibitors as anti-gout agents from natural products, various chromatographic separations of the ethyl acetate-soluble fraction of Aster glehni (AGEF) led to the isolation of five new caffeoylglucoside derivatives, namely 6'-O-caffeoyl-(6S,9R)-roseoside (1), 6'-O-caffeoylampelopsisionoside (2), 6'-O-caffeoylsonchuinoside C (3), 6'-O-caffeoyldihydrosyringin (4), and (2E)-2-methyl-but-2-ene-1,4-diol-6'-O-caffeoyl-1-O-beta-glucopyranoside (glehnoside, 5), together with 13 known compounds. The absolute stereochemistry of the 6'-O-caffeoylsonchuinoside C(3) was established with the help of spectroscopic analyses, enzymatic hydrolysis, and Mosher's method, as well as in comparison with literature data. All isolated substances were determined for their inhibitory activities on uric acid production by the xanthine/XOD system. Among them, 4,5-O-dicaffeoylquinic acid methyl ester (12) showed the most potent inhibitory activity with an IC50 value of 2.6 +/- 0.1 mu M, which was comparable to that of allopurinol used as a positive control. Furthermore, hypouricemic effects of AGEF were assessed by measuring serum uric acid levels 3 h after potassium oxonate treatment (250 mg/kg, i.p.) to induce hyperuricemia in rats. When preadministered orally once a day at doses of 50, 100, and 300 mg/kg for 7 days, AGEF reduced the potassium oxonate-induced elevated serum uric acid level by 15.4, 39.8, and 32.3%, respectively. The results suggest that AGEF has the potential to be a new source of agents for the prevention and/or treatment of hyperuricemia and gout.
Keywords: BETA-D-GLUCOSIDES; XANTHINE-OXIDASE; POTASSIUM OXONATE; URIC-ACID; GLYCOSIDES; GOUT; ANTIOXIDANT; INHIBITORS; RODENTS